The selection of scanning strategy and annealing schedule for the optimization of texture and magnetic properties of Fe-3.5 wt%Si alloy parts fabricated by laser powder bed fusion - Meng, Fanbo (2025)
By careful selection of the scanning strategies (SS), researchers in this study were able to realize a simple algorithm to control the grain orientation with the extremely strong Rotated Cube and Cube texture obtained in laser powder bed fusion (LPBF) fabricated electrical steel. Microstructure was characterized by optical microscopy (OM) and electron backscatter diffraction (EBSD), and quasi-static magnetic properties were measured through DC closed magnetic circuit method. The findings show that sufficient remelting with a stable thermal field induces a strong < 001 > parallel to the building direction (BD) texture by promoting epitaxial growth aligned with BD. In-plane grain orientation rotates from < 011 > //X-axis towards < 001 > //X-axis (X-/Y-axis denote length/width directions of samples, respectively) with the reduction of the track length. By promoting < 001 > //BD and < 001 > //X-axis textures, double scanning introduced a strong Cube texture in the D-XY samples (double scan along X-axis and Y-axis successively in one layer). Sample heat treatment (HT) considered in this study only induced abnormal grain growth. Coarse grains and desirable texture components contribute to improving permeability during magnetization of domain wall displacement and rotation of the magnetization vector, respectively, and coarse grains also reduce coercivity (Hc). Benefitting from corresponding microstructure, D-XY samples annealed at 1000℃ for 2 h exhibited the highest maximum relative permeability (μrmax) of 4450, while S-X samples (single scan along X-axis) annealed at 1150℃ for 4 h showed the highest initial permeability (μi) of 0.34 mH/m and lowest Hc of 44.5 A/m in this study. This study provides an insight into the relationship between the manufacturing route, microstructure, and magnetic properties of LPBFed electrical steel and establishes a firm basis for controlling the texture components and grain morphology of Fe-3.5 wt%Si via judicious selection of SS and HT.